Silicon pools, fluxes and the potential benefits of a silicon soil amendment in a nitrogen-enriched tidal marsh restoration - Staver, L. W.; Stevenson, J. C.; Cornwell, J. C.; Nidzieko, N. J.; Staver, K. W.; Owens, M. S.; Elmer, W. H. (Frontiers in Ecology and Evolution, 2023)
Tidal marshes are important sites of silicon (Si) transformation, where dissolved Si (DSi) taken up by macrophytic vegetation and algal species is converted to biogenic silica (BSi), which can accumulate in the soil, be recycled within the marsh, or be exported to adjacent coastal waters. The role of restored and created tidal marshes in these processes is not well understood, nor is the impact of nutrient enrichment at either the plant or ecosystem level. Here, Si fluxes were examined to develop a Si mass balance in a nitrogen (N) -enriched marsh created with fine-grained dredged material from the Chesapeake Bay, USA. In addition, the effectiveness of Si soil amendments to ameliorate the negative effects of excess nitrogen on Spartina alterniflora was examined through laboratory and field experiments. Silicon was exported to the estuary as DSi (49 g m-2 y-1) and BSi (35 g m-2y-1) in stoichiometric excess of nitrogen and phosphorus. Rapid recycling of Si within both marsh and the tidal creeks appeared to be important in the transformation of Si and export from the marsh. Enhanced macrophyte SiO2 tissue concentrations were observed in the field experiment, with end-of-season mean values of 2.20–2.69 % SiO2 in controls and 2.49–3.24 % SiO2 in amended plots, among the highest reported for S. alterniflora; however, improved plant fitness was not detected in either experiment. Thus, tidal marshes created with a fine-grained, N-rich dredged material appear to function as a rich source of Si to the restored marsh and local estuarine environment, an overlooked ecosystem service. Soil Si amendments, however, did not appear likely to alleviate N-induced stress in S. alterniflora.